A Companion to World Literature 2019
DOI: 10.1002/9781118635193.ctwl0050
|View full text |Cite
|
Sign up to set email alerts
|

Erotic Words, Sacred Landscapes, Ideal Bodies: Love and Death in the Song of Songs

Abstract: The Song of Songs, composed probably in the third century bce , is one of the most influential poems in the Western erotic and mystical traditions, by virtue of its appearing in the Bible. It is a dialogue between two lovers in an idyllic pastoral landscape, seemingly without relation to the rest of the sacred text. It is, however, a critique of the biblical tradition, whose implicit question is: what was it all worth? For the Song, the answer is that love alone guarantees an ambiguous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
3
0
1
Order By: Relevance
“…Hunt (2008) underscored that it was very scant in the Bible that physical beauty was lauded as something eternal through extravagant similes. The findings of this study also corroborated the study of Landy (2020) that woman in the Song was described as more active and dynamic than man. She further evidenced that the woman is the center of the poetry and the more commanding character.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Hunt (2008) underscored that it was very scant in the Bible that physical beauty was lauded as something eternal through extravagant similes. The findings of this study also corroborated the study of Landy (2020) that woman in the Song was described as more active and dynamic than man. She further evidenced that the woman is the center of the poetry and the more commanding character.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, Gault (2019), analyzing the Song of Songs' body metaphors, concluded that the metaphors portrayed the forms and functions of the lovers' bodies as well as the beauty concept in ancient Israel. Landy (2020) unearthed The authors of the present study found that the investigations applying Conceptual Metaphor Theory that focus on the similes of man and woman in the whole Songs of Songs are still scant. The previous studies on the Song of Songs have discussed the metaphors and similes in terms of other themes, like body imagery (Gault, 2019), sacred landscapes (Landy, 2020), of certain verses, like Songs 4,4 (Verde, 2016(Verde, , 2018, or of its functions, like to display motif of virility (Hunt, 2008).…”
Section: A Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Landy mendiskusikan ketidakstabilan gender dalam kitab Kidung Agung dan ia mempertanyakan budaya patriarki untuk menciptakan ruang maternal yang rentan bagi keintiman kekasih. Ruang tersebut disebutnya sebagai ruang imajinasi puitis yang lebih nyata daripada dunia sehari-hari (Landy, 2019). Sedangkan menurut Darmaraj, kitab Kidung Agung meninggalkan, bahkan menolak, budaya yang diakomodasi oleh teks Perjanjian Lama lainnya yang menciptakan hak prerogatif pria dari kecemburuan dalam cinta romantik (Dharamraj, 2018).…”
Section: Pendahuluanunclassified